Experimental Investigation of Glycerol Derivatives and C1–C4 Alcohols as Gasoline Oxygenates - André L. Olson; Martin Tunér; Sebastian Verhelst (Energies, 2024)
Certain oxygenated compounds, when blended with gasoline, have the ability to inhibit the occurrence and decrease the intensity of engine knock, helping improve engine efficiency. Although ethanol has had widespread use as an oxygenate, higher alcohols, such as butanol, exhibit superior properties in some respects. Besides alcohols, glycerol derivatives such as glycerol tert-butyl ether (GTBE), among others, also have the potential to be used as gasoline oxygenates. This work provides a direct comparison, performed on a modified Waukesha CFR engine, of C1–C4 alcohols and the glycerol derivatives GTBE, solketal, and triacetin, all blended with a gasoline surrogate in different concentrations. The tests focused on how these oxygenated compounds affected the knocking behavior of the fuel blends, since it directly impacts engine efficiency. The test matrices comprised spark-timing sweeps at two different compression ratios, at stoichiometric conditions and constant engine speed. The results showed that, in general, the C1–C4 alcohols and the glycerol derivatives were effective in decreasing knock intensity. n-Butanol and solketal were the noteworthy exceptions, due to their demonstrated inferior knock-inhibiting abilities. On the other hand, isopropanol, isobutanol, and GTBE performed particularly well, indicating their potential to be used as gasoline oxygenates for future engines, as alternatives to ethanol.